PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN PERILAKU KADER DALAM PEMANTAUAN TUMBUH KEMBANG BALITA - Astuti Anggraini, Tyas Ning Yuni; Ekawati (MEDIA ILMU KESEHATAN, 2019)
Background: One of the health development in Indonesia in the period of 2015-2019 was focused on reducing the stunting of under-fives. One of the government's tasks to overcome stunting is to oversee the growth and development of infants. This task reaches the level of basic health services, namely Posyandu which is carried out by trained cadres. Objective: to determine the effect of providing health education to the knowledge and behavior of Posyandu cadres in monitoring the growth and development of toddlers in Sukoharjo Methods: This type of research uses Quasi Experiment. The population in this study were all Posyandu cadres in Sukoharjo Village. The population is 120 cadres. Sampling technique with total sampling. The questionnaire used in this study used a closed questionnaire. Data analysis using the Wilcoxon Signed Rank Test Results: Most respondents have sufficient behavior as much as 96 respondents (80%), whereas after being given health education there is an increase in the good category of 96 people (80%). If seen from the Wilcoxon rank test, a p-value of 0,000 <0.05 is obtained, meaning that there are differences in behavior among respondents after being given health education. Conclusion: There is an influence of health education on knowledge and behavior in monitoring growth and development in the village of Sukoharjo